2022
DOI: 10.1136/bmjopen-2021-051496
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrus and iStent microinvasive glaucoma surgery implants in combination with phacoemulsification for treatment of open-angle glaucoma: systematic review and network meta-analysis

Abstract: ObjectivesTo compare the efficacy and safety of two Schlemm’s canal-based microinvasive glaucoma surgery (MIGS) devices, the Hydrus Microstent and the iStent Trabecular Bypass combined with phacoemulsification for treatment of open-angle glaucoma.DesignSystematic review and network meta-analysis.MethodsLiterature searches were conducted on PubMed, Web of Science, Cochrane Library and ClinicalTrials.gov to identify randomised controlled trials (RCTs) assessing the Hydrus or the iStent implantation combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…There is now a wide array of potential MIGS therapies with varying mechanisms of action. The majority of clinical studies investigating MIGS have focused on individual devices, with fewer studies of paired procedures or comparisons of different procedures [ 20 , 21 , 25 , 26 ]. A greater understanding of how MIGS procedures can be combined, or their comparative utility, may reveal potential [ 27 ] new treatment approaches for patients who might otherwise experience disease progression requiring invasive filtration surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is now a wide array of potential MIGS therapies with varying mechanisms of action. The majority of clinical studies investigating MIGS have focused on individual devices, with fewer studies of paired procedures or comparisons of different procedures [ 20 , 21 , 25 , 26 ]. A greater understanding of how MIGS procedures can be combined, or their comparative utility, may reveal potential [ 27 ] new treatment approaches for patients who might otherwise experience disease progression requiring invasive filtration surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The IOPR data were used directly if available in the original study. If not given, the IOPR was calculated from the given data with the following formulas: IOPR = IOP baseline − IOP final , SD IOPR = leftSDbaseline2+SDendpoint2SDbaseline×SDendpoint1/2 (Luo et al., 2023). If data were not presented as mean ± standard deviation, Hozo et al.…”
Section: Methodsmentioning
confidence: 99%
“… 44 Results of a meta-analysis of six prospective randomised clinical trials (1397 patients) concluded findings similar to the COMPARE study, with rank probability analysis revealing phacoemulsification combined with Hydrus implantation may provide better IOP control compared to implantation of one or two iStents, albeit with a higher incidence of focal PAS. 45 This analysis also determined that the implantation of Hydrus and two iStents enacted a greater probability of reaching medication-free status when compared to one iStent and standalone phacoemulsification. 45 When compared to the implantation of two iStents in ex-vivo studies, the Hydrus microstent has been suggested to provide additional benefits in reducing aqueous outflow resistance.…”
Section: Hydrus Vs Istentmentioning
confidence: 99%
“… 45 This analysis also determined that the implantation of Hydrus and two iStents enacted a greater probability of reaching medication-free status when compared to one iStent and standalone phacoemulsification. 45 When compared to the implantation of two iStents in ex-vivo studies, the Hydrus microstent has been suggested to provide additional benefits in reducing aqueous outflow resistance. 46 In a study of 12 pairs of cadaveric eyes, Hays et al observed a greater increase in outflow facility (73% vs 34%) across a greater range of perfusion pressures (20–50 mmHg vs 40 mmHg only) with the Hydrus microstent compared to two iStents, likely due to greater collector channel access.…”
Section: Hydrus Vs Istentmentioning
confidence: 99%